Can Facebook groups enhance continuing professional development of teachers? Lessons from Kenya - Bett, Harry; Makewa, Lazarus (Asia-Pacific Journal of Teacher Education, 2020)
Continuing Professional Development (CPD) for teachers in Kenya suffers from challenges such as inadequate resources, poor planning, competing interests, among others. Besides being traditional in approach, most CPD sessions are far between to be meaningfully helpful. With increasing uptake of technology and number of social media users in Kenya, Facebook can be a potential platform to enhance teachers’ professional development. This exploratory cross-sectional survey focussed on discussions teachers had in the month of February 2015 on one Facebook Group named ‘Teachers of English’. A directed content analysis of the 647 posts following Shulman’s category of teacher knowledge base revealed that interactions on the group centred on the teaching of English and Literature, as well as on other education-related matters. This study concludes that that Facebook Groups can be fertile avenues for teachers’ ongoing professional development, especially in developing countries where such opportunities are scarce.
Keywords: Content analysis; Education--Teaching Methods And Curriculum; English teachers; Facebook Groups; Kenya; Professional development; Social networks; Teacher education; Teachers; __:import:02; __:match:final; __:matched; __:study_id:2425933; __finaldtb; professional development

The cascade model of teachers’ continuing professional development in Kenya: A time for change? - Bett, Harry Kipkemoi (Cogent Education, 2016)
Kenya is one of the countries whose teachers the UNESCO (2015) report cited as lacking curriculum support in the classroom. As is the case in many African countries, a large portion of teachers in Kenya enter the teaching profession when inadequately prepared, while those already in the field receive insufficient support in their professional lives. The cascade model has often been utilized in the country whenever need for teachers’ continuing professional development (TCPD) has arisen, especially on a large scale. The preference for the model is due to, among others, its cost effectiveness and ability to reach out to many teachers within a short period of time. Many researchers have however cast aspersions with this model for its glaring shortcomings. On the contrary, TCPD programmes that are collaborative in nature and based on teachers’ contexts have been found to be more effective than those that are not. This paper briefly examines cases of the cascade model in Kenya, the challenges associated with this model and proposes the adoption of collaborative and institutionbased models to mitigate these challenges. The education sectors in many nations in Africa, and those in the developing world will find the discussions here relevant.